KEEFEKTIFAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTU MEDIA WORDWALL TERHADAP HASIL BELAJAR IPAS SISWA KELAS III SDN KARANGTEMPEL SEMARANG - Devitasari, Anis; Huda, Choirul; Wijayanti, Arfilia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
A study has been successfully conducted on the effectiveness of the Problem Based Learning model assisted by Wordwall media on the learning outcomes of third-grade students of SDN Karangtempel Semarang. This study aims to determine the effectiveness of the Problem Based Learning (PBL) learning model assisted by Wordwall media on the learning outcomes of third-grade students of SDN Karangtempel Semarang. This study uses a quantitative approach with a pre-experimental design in the form of One Group Pretest-Posttest Design. The subjects of the study were all 22 third-grade students of SDN Karangtempel Semarang. Data collection techniques were carried out through observation, interviews, tests, and documentation. The research instruments in the form of pretest and posttest questions were used to measure student learning outcomes before and after the application of the PBL learning model assisted by Wordwall media. The data obtained were analyzed using the Paired Sample T-Test. The results showed an increase in students' learning outcomes in science after being given treatment. The average pretest score was 56.9 with a learning completion percentage of 14%, while the average posttest score increased to 88.6 with a learning completion percentage of 91%. The t-test results show that the t-value is 19.352, so H0 is rejected and Ha is accepted. Thus, it can be concluded that the Problem Based Learning (PBL) learning model assisted by Wordwall media is effective in improving the science learning outcomes of third-grade students at SDN Karangtempel Semarang.